“UNVEILING THE CHALLENGES OF CHILDHOOD AND EDUCATION IN THE WORLD OF CHARLES DICKENS” - Bakhranov Bekhruz Abduxalil o‘g‘li (TADQIQOTLAR.UZ, 2024)
Annotation: This article delves into the intricate portrayal of childhood and education in the literary world of Charles Dickens. It explores the challenges faced by children, particularly those from impoverished backgrounds, and the societal injustices that hinder their access to quality education. Through an analysis of Dickens’s novels, such as “Oliver Twist,” “David Copperfield,” and “Great Expectations,” the article sheds light on the harsh realities of Victorian-era schooling, child labor, and the impact of social inequality on educational opportunities. By unraveling the complexities of Dickens’s narratives, the article offers insights into the enduring relevance of his themes in contemporary discussions on childhood, education, and social justice.